SHALAT QABLIYAH DAN BA’DIYAH DALAM PANDANGAN ULAMA HADIS - Aniqoh; Mahmud Nasir (STAI Syubbanul Wathon Magelang, 2021)
Hadith has a central position in Islam. It is the secondsource after the Qur'an, which functions to detail the messages ofthe Qur'an which are mujmal, so that clear information is obtainedin carrying out daily amaliah worship, including qabliyah andba'diyah prayers. However, in fact, the hegemony of fiqh thought isdeeper than understanding the hadith in determining the practiceof worship of Muslims, especially Indonesian Muslims. Fiqh seemsto be the first and main benchmark in dealing with problems.Therefore, the researcher will present how the hadith actuallydescribes the af'aliyah of the Messenger of Allah regarding the pureqabliyah and ba'diyah prayers in accordance with the views ofhadith scholars. In this study, the method used is the thematicmethod of hadith. That is by collecting the same hadiths thatdiscuss the qabliyah and ba'diyah prayers. In this study, beforemoving on to understanding hadith, the validity of the quality ofhadith will be explained, so that it can be used as a guideline. Thelocal hadith research is the pole of al-tis'ah, while the understandingis taken from the sharh of the hadith books. From the results of thestudy, it was explained that the Prophet carried out the qabliyahand ba'diyah prayers. Qabliyah dawn as much as two raka'at andafter that he slept lightly until the muezzin iqamat. QabliyahDhuhur he performs two raka'at and sometimes four raka'at. Whileba'diyah Dhuhur he carried out two raka'at. Qabliyah 'Asar heperformed four raka'at with two greetings. For qabliyah MaghribRasulullah ordered to run it for those who want, but with a note donot consider it as a strengthened Sunnah. While ba'diyah Maghrib,he runs two raka'at. As for ba'diyah 'Isha, he performed two raka'at. ",